Utilisation of papaya peel flour as source of fibre in festive cookie, pineapple tart/ Siti Sabariah Buhar, Fatimah Najihah Baderol Allam and Fadhilah Jailani - Buhar, Siti Sabariah; Baderol Allam, Fatimah Najihah; Jailani, Fadhilah (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
A pineapple tart with good source of fibre was developed by utilising papaya peel flour as part of the ingredients to increase the fibre content. Fresh papaya was peeled, cut into small pieces, further washed, oven dried and finely ground to powder form. The papaya peel flour contained 12.2% crude fibre content and further used in festive cookie formulation. The new pineapple tart was formulated by substituting 4% and 10% papaya peel flour with wheat flour in the present investigation. The percentage of moisture, ash, fat, protein, crude fibre, and total carbohydrate content of all pineapple tart formulations were determined. The average percentage of crude fibre in 1g of new developed pineapple tart with 10% papaya peel flour substitution sample is 4.1%. This followed by the new developed pineapple tart with 4% papaya peel flour substitution sample which contain 3.8% crude fibre. The experimental result revealed that the new developed pineapple tart contains significant amount of crude fibre content in comparison to the control pineapple tart which improves its nutritional characteristics. Sensory evaluations of all developed pineapple tart were carried out. It was found that 4% papaya peel flour substitution in pineapple tart formulation was accepted by the panelist. Therefore, 4% papaya peel flour based formulated festive cookie, pineapple tart proves enhanced nutritional properties.